Spatial Study of Maleo Bird Habitat Area Change in Sulawesi - Kumaji, Syam S; Wantogia, Misnawaty; Mohamad, Nurdin; SM, Farid; Yusuf, Daud; Baderan, Dewi Wahyuni K; Hamidun, Marini Susanti; Rahim, Sukirman; Dunggio, Iswan (Jurnal Biologi Tropis, 2024)
Maleo (Macrocephalon maleo), a unique Sulawesi endemic bird, is threatened by habitat loss. This study aims to analyse changes in maleo habitat areas in Sulawesi using spatial data and propose effective conservation measures. Spatial data in the form of maleo home range maps (IUCN) were used for overlay analysis. The results of the overlay analysis were compared with land cover data to identify changes in maleo habitat area. Of the total area of approximately 884,040 hectares, 14.13% or 124,887.63 hectares have been converted to agricultural land. The construction of new settlements has affected 0.46% or 4,087.5 hectares of the habitat. In addition, plantations have occupied 2.82% or 24,965.92 hectares of the maleo habitat area. Changes to maleo habitat areas in Gorontalo are significant, with agricultural land conversion, settlement development, and plantations being the main threats. Effective conservation efforts should focus on habitat restoration, law enforcement, community education, and the development of environmentally friendly economic alternatives.